Motivasi Kinerja Pustakawan Universitas Atma Jaya Yogyakarta Setelah Keluarnya Jabatan Fungsional Pustakawan - Nugrohoadhi, Agung (Jurnal Ilmu Perpustakaan & Informasi KHIZANAH AL-HIKMAH, 2014)
As the organizer of Universitas Atma Jaya Yogyakarta (UAJY), offering to UAJYâs librarians to get chance to switch profession from administrative to become librarian in which the candidate should of course be qualified by YSR. The objective of this conversion is to enhance library services. Librarian is not just about âbook keepersâ as many people defined, but its profession is expected to give proactive service to the end-users. FJP in UAJY has attracted librarians who have already been working in the library to re-consider on their profession. UAJYâs librarians demanded advanced services and reward based on what was signed in UU No. 43 Tahun 2007 tentang Perpustakaan.